Fluoroscopic balloon diameter measurement at different pressures during Eustachian balloon dilation. (12th September 2018) - Kang, Byung Chul; Kang, Woo Seok; Park, Jun Woo; Park, Jung‐Hoon; Kim, Kun Yung; Song, Ho‐Young; Park, Hong Ju
Abstract : Objectives: To measure the diameter of inflated balloons at different pressures during Eustachian tube (ET) balloon dilation under fluoroscopic guidance. Design: Prospective cohort study. Setting: Tertiary academic referral centre. Participants: Eighteen patients who underwent ET balloon dilation with use of a balloon catheter, 20 mm long and 6 mm in diameter, under combined endoscopic and fluoroscopic guidance. Main outcome measures: Degrees of inflation at three different portions (proximal, middle and distal) of the balloon at controlled pressures (3, 5, 8 and 10 atmospheres [atm]) and at the maximum pressure manually applied. Results: The mean proximal, middle and distal diameters of the inflated balloons were 5.3 ± 0.4 mm, 5.3 ± 0.4 mm and 4.9 ± 0.5 mm at 10 atm. The distal diameters were significantly smaller than middle and proximal diameters at all the pressures ( P  < 0.01). When compared to the distal diameter (100%, 4.9 ± 0.5 mm) at 10 atm, the distal diameters were 73% (3.6 ± 0.6 mm) at 3 atm, 88% (4.3 ± 0.5 mm) at 5 atm and 96% (4.7 ± 0.4 mm) at 8 atm. The distal diameter (4.1 ± 0.3 mm) at the maximum pressure manually applied was in between those at 3 and 5 atm. Conclusions: The distal diameter of the balloon increased significantly as a function of the pressure and most (88%) inflation occurred at a low pressure of 5 atm, which was sufficient to inflate the distal diameter of the balloon more than 3 mm. The manual pressurisation could inflate a balloon by as much as could be expected, at between 3 and 5 atm.